Image Analysis of Periapical Radiograph for Bone Mineral Density Prediction - Rini Widyaningrum; Sri Lestari; Ferry Jie (Institute of Advanced Engineering and Science, 2018)
Osteoporosis is a systemic skeletal disease. Parameter from any bone site in the body has possibility to be developed as a predictor of osteoporosis. The alteration in the mandible trabecular bone is visible in periapical radiographs. The aim of this study was to correlate the area parameter and the integrated density of periapical radiograph with bone mineral density. Image analysis of periapical radiograph i.e. measurement of area parameter and integrated density was done on Region of Interest (ROI) by using canny edge detection method. Result of this study showed that the area parameter has asignificant (α<0.05) negative correlation with the bone mass density (BMD) of the lumbar spine (r = -0.371) and T-score of the lumbar spine (r = -0.383). The linear regression test showed that the area parameter only can be used to predict T-score of the lumbar spine (F=5.822, α<0.05). The integrated density showed a significant (α < 0.05) negative correlation with T-score of hip (r = -0.332) and T-score of lumbar spine (r = -0.377). It can be concluded that the area parameter can be used as one of input parameters for computer-aided system of osteoporosis early detection by using periapical radiograph.